The Role of Social Media as a Resource for Mental Health Care - Ivan Herrera-Peco; Invención Fernández-Quijano; Carlos Ruiz-Núñez (MDPI AG, 2023)
One of the major lessons learned from the COVID-19 pandemic was the importance of caring for the mental health of populations [...]